Menstrual Hygiene Awareness and its Managementamong school going Adolescent Girl Students - Awtar Kishan Kaul Dr.Manjiri Bakshi Precious Gona Shivam (International journal of economic perspectives, 2023)
Girls’ enrolment in schools is steadily showing an upward spirallingtrend with the increasing awareness among parents and their wards for better education and its accompanied benefits’.In the wake of this emerging social reality, there is a pressing need for schools to go all out with total preparedness for handling girl’s issues especially menstrual related problems and hygiene.